Bilateral cataract induced by unilateral UVR‐B exposure – evidence for an inflammatory response. (28th March 2012) - Meyer, Linda M.; Löfgren, Stefan; Holz, Frank G.; Wegener, Alfred; Söderberg, Per
Abstract. Purpose: To investigate whether unilateral in vivo UVR‐B exposure of one eye affects the fellow eye in a co‐cataractogenic, sympathetic reaction and to determine whether an inflammatory response could be involved in the pathogenesis. Methods: C57BL/6 mice were unilaterally exposed in vivo to UVR‐B for 15 min. In the group of 24 animals each received 0×/2×/3×/or 4× cataract threshold equivalent dose. Following 48‐hr UVR‐B exposure, cataract morphology was documented in dark‐field illumination photography, and light scattering was quantified, in both lenses in vitro. Serum levels of pro‐inflammatory cytokines IL‐1ß, IL‐6 and TNF‐α were analysed with ELISA. Immunohistochemistry was performed for inflammatory infiltration in exposed and contralateral eyes. Results: UVR‐B exposure induced cataract in all exposed lenses. There was additionally a significant UVR dose–dependent increase in light scattering in the lenses of the non‐exposed fellow eye. Inflammatory infiltration was detected immunohistochemically in the anterior segment of both eyes. IL‐1β serum concentration increased with increasing UVR‐B exposure dose. There was a similar trend for serum IL‐6 but not for TNF‐α. Conclusion: Unilateral UVR‐B exposure to one eye is associated with intraocular inflammation and an increase in lens light scattering also in the unexposed, fellow eye. A resulting systemic inflammatory response might be mediated by IL‐1β and possibly IL‐6. The finding that an inflammatory response may play a role in UVR‐B‐induced cataract development might initiate new strategies in the prevention of the disease.